Evaluation of Egg Quality Traits of Three Indigenous Chicken Ecotypes Kept Under Farmers’ Management Conditions - Markos , S.; Belay, B.; Astatkie, T. (International Journal of Poultry Science, 2017)
Background and Objective: Understanding egg quality traits of indigenous chicken ecotypes under farmers’ management conditions is very important for designing and implementing environment friendly and community based holistic genetic and performance improvement strategies. This study was conducted to compare three ecotypes (lowland, midland and highland) in Tigray, Ethiopia in terms of their external and internal egg quality traits and to determine relationships among these traits. Materials and Methods: From each ecotype, 50 fresh eggs were used to measure external egg quality traits (egg weight, shell weight, shell ratio, egg length, egg width and egg shape index) and internal egg quality traits (albumen weight, albumen ratio, yolk weight, yolk ratio, albumen height, yolk height, yolk to albumen ratio, Haugh unit and yolk color). One-way ANOVA was used to compare the ecotypes and correlation analysis was used to determine relationships among the traits. Results: Three ecotypes were significantly different on all traits except shell ratio and yolk color. In all other external traits, highland ecotype had higher mean values than midland and lowland had the lowest mean values. Highland also had higher mean values in the internal traits other than albumen ratio whereas lowland had higher mean values than both highland and midland ecotypes. The strength of the significant correlations among the external traits, among internal traits and between external and internal traits varied with ecotype. Conclusion: The differences in the quality of local chicken eggs from the three ecotypes suggest that there is a need for customized genetic and performance improvement strategies.